2016
DOI: 10.1007/s00262-016-1925-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased PD-L1 and T-cell infiltration in the presence of HLA class I expression in metastatic high-grade osteosarcoma: a rationale for T-cell-based immunotherapy

Abstract: IntroductionImmunotherapy may be an excellent choice for treating osteosarcoma given its exceptionally high genomic instability, potentially generating neoantigens. In this study, we aim to investigate the HLA class I expression, PD-L1 and tumour-infiltrating lymphocytes in primary osteosarcomas and relapses/metastases, as well as their changes during disease progression.Materials and methodsTumour samples from multiple stages of the disease (pretreatment biopsies, surgical resections of primary osteosarcomas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 33 publications
5
94
1
Order By: Relevance
“…In the present study, we observed that Evodiamine caused a significant decrease in the expression of cyclin B1, Cdc25c, and Cdc2, favoring cell cycle arrest at G2/M phase. Metastasis of osteosarcoma is very challenging to manage; therefore, it is important to discover molecules that can inhibit the metastasis of osteosarcoma cells [21]. In the present study, we observed that Evodiamine inhibited the migration and invasion of U2OS osteosarcoma cells.…”
Section: Discussionsupporting
confidence: 53%
“…In the present study, we observed that Evodiamine caused a significant decrease in the expression of cyclin B1, Cdc25c, and Cdc2, favoring cell cycle arrest at G2/M phase. Metastasis of osteosarcoma is very challenging to manage; therefore, it is important to discover molecules that can inhibit the metastasis of osteosarcoma cells [21]. In the present study, we observed that Evodiamine inhibited the migration and invasion of U2OS osteosarcoma cells.…”
Section: Discussionsupporting
confidence: 53%
“…Although current concepts hold that PD-L1 expression may serve as a marker of lymphocyte activation and production of interferon-c within the tumor microenvironment, 57 we did not observe a correlation between lymphocyte infiltration and PD-L1 expression in this data set. 54 Together, our data demonstrate that significant subsets of pediatric tumors express PD-L1, either on the tumor itself or in the microenvironment. Previous studies have reported a predominance of macrophages in pediatric tumors 58,59 ; whereas, in our samples, a minority of tumors demonstrated macrophage infiltration, and these macrophages often expressed PD-L1.…”
Section: Discussionmentioning
confidence: 55%
“…A study by Chowdhury et al found higher rates of PD-L1 expression in a series of 115 pediatric tumors, 55 but their study relied on an antibody that was not validated for the detection of PD-L1. 30,31,54 Third, emerging evidence suggests that pediatric cancer genomes evolve extensively after exposure to chemoradiotherapy and attain significantly larger mutational burdens. Although current concepts hold that PD-L1 expression may serve as a marker of lymphocyte activation and production of interferon-c within the tumor microenvironment, 57 we did not observe a correlation between lymphocyte infiltration and PD-L1 expression in this data set.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, osteosarcoma cells express B7-H3 which is correlated with the aggressiveness of the disease and metastatic capacity [85,86]. Program Death Ligand-1 (PDL-1) and PDL-2 were also detectable in all osteosarcoma cases [89][90][91][92][93][94].…”
Section: Lymphocytes Subpopulations In Osteosarcoma and Therapeutic Imentioning
confidence: 99%